2021
DOI: 10.1097/prs.0000000000008627
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Use of Power Doppler Ultrasound in the Imaging of Peripheral Nerve Compression Neuropathy

Abstract: Background: Power Doppler ultrasonography has been used as an adjunct in the diagnosis of peripheral nerve compression neuropathy. To better characterize its sensitivity and specificity, the authors performed a systematic review of its use in carpal and cubital tunnel syndrome diagnosis. Methods: The authors systematically reviewed published literature on the use of power Doppler ultrasound to diagnose peripheral compression neuropathy using Ovid MEDLINE, Embase.com, Scopus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…14,29 Advances in electrodiagnosis and imaging have supported preoperative surgical planning, but significant intraoperative decisionmaking remains necessary. 14,30,31 Therefore, decision to perform a simple in situ decompression vs more extensive decompression remains elusive. Mechanomyography may help validate neurological deficits and predict outcomes, aiding in such decisions.…”
Section: Discussionmentioning
confidence: 99%
“…14,29 Advances in electrodiagnosis and imaging have supported preoperative surgical planning, but significant intraoperative decisionmaking remains necessary. 14,30,31 Therefore, decision to perform a simple in situ decompression vs more extensive decompression remains elusive. Mechanomyography may help validate neurological deficits and predict outcomes, aiding in such decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Fowler et al, in their meta-analysis, showed that the Sn for diagnostic ultrasound ranged between 0.57 and 0.98 and the Sp ranged from 0.63 to 1.00 [ 58 ]. Landau et al reviewed the use of power Doppler ultrasound and found that Sn/Sp for diagnosing CTS showed high levels of variability, reporting a range of 0.02-0.93 for Sn and an Sp of 0.89-1.00 [ 59 ]. The lack of an accepted diagnostic gold standard or reference standard for CTS likely contributes to this diagnostic uncertainty and serves as a caution against using individual tests in isolation to make the diagnosis.…”
Section: Reviewmentioning
confidence: 99%
“…4 ). 8 , 24 , 25 A systematic review by Landau et al 26 found that PDUS is unreliable as a screening test but increases the diagnostic accuracy of ultrasound in compressive neuropathies. The analysis of PDUS waveforms provides a surrogate for intraneural blood flow by assessing the velocity of flow.…”
Section: Diagnosis Of Compressive Neuropathiesmentioning
confidence: 99%